Urban regeneration and retail in Birmingham (Ciudades, 2018)
In the last twenty years, Birmingham’s city centre and its urban environment have been radically transforming. During the nineties in England, a decisive change in the central government was registered, as much in the matter of retail policies as in the one of mobility. City centre has been regenerated by promoting and valorising the retail activities. Liberal ideas that succeeded in the eighties were finished and a compact model for city took place, giving preference to the mobility and sustainability.Birmingham experience is a reference model because the retail core has been transformed with a strong commercial mission. “Birmingham. Europe’s new shopping capital”, is the mission, and Selfridges’s flagship department store the new city centre landmark. “Multi-block-shopping-centre-city”, where no cars are allowed in traditional pedestrian public open spaces between commercial buildings, but where those primary spaces have been privatized and managed as a part of the new “shopping experience”.
Keywords: Birmingham; shopping centre-city; urban management